Toys - Bryant-Mole, Karen (Wayland Publishers Ltd, 1994)
The captivating photographs of Picture This! help introduce primary learners to a variety of themes and basic topics. Each book features simple text and clear labels describing interesting collections of objects. Includes an easy to use glossary.
Keywords: Juvenile literature- Non-Fiction